KNITWEAR: FROM CLOTHING TO FURNITURE - Raycheva, Regina; Angelova, Desislava (Innovation in Woodworking Industry and Engineering design, 2018)
The paper is focused on a tendency, clearly defined these last years, of the application of knitting technique in furniture design. Traditions and contemporary knitting techniques are researched, as well as materials used. Analysis is made of their implementation in furniture. A number of examples are researched in an attempt to classify the application of knitwear in different furniture types, their function, as well as the most often used techniques and materials. By means of selection, classification, visual identification and comparative morphologic analysis, the potential of this technique is revealed.